Anthropometric and physiological characteristics in young afro-caribbean swimmers: a preliminary study - Hue, O.; Antoine-Jonville, S.; Galy, S.; Blonc, S. (International Journal of Sports Physiology and Performance, 2013)
The authors investigated the anthropometric and physiological characteristics of young Guadeloupian competitive swimmers in relation to swimming performance and compared the abilities of these children with those of the young white swimmers reported in the literature. All 2004 competitive swimmers between 10 and 14 y old (126 children, 61 boys and 65 girls, 12.0 ± 1.3 y) from Guadeloupe underwent anthropometric measurements and physiological and performance testing. Six boys on the French national swimming team are referred to hereafter as the 2011 elite subgroup. Anthropometric parameters, a jump-and-reach test, glide, and estimated aerobic power (eVO2max) were assessed in terms of swimming-performance analysis through a 400-m test. This study demonstrated that the Guadeloupian swimmers had more body fat than most age-matched white swimmers but had very poor hydrostatic lift; they had higher peak jump height and they swam as well as their white counterparts. The variability in 400-m performance between subjects was best described by glide, age, and eVO2max. Compared with the group of boys with the same age, the 2011 elite subgroup was significantly better for arm span, peak jump height, glide, and 400-m and 15-m performances. Further research is needed to investigate motor organization and energy cost of swimming in Afro-Caribbean swimmers.